Revitalization of Food Barns to Support Community and National Food Security - Putri Wulansari; Mhd. Rasidin; Doli Witro (Pusat Penelitian, Badan Keahlian DPR RI, 2021)
After implementing the green revolution policy and the existence of the National Logistics Agency (Bulog) as an institution whose role is to maintain food stability, the people’s food barns have lost their existence. The impact of the decline in the existence of community food barns, in the long run, causes food instability in Indonesia. This is due to several factors, including the conversion of agricultural land into industrial land, the use of inorganic fertilizers which causes soil fertility to decline resulting in reduced crop yields, Bulog’s transfer of function from a government entity to a state-owned enterprise/Perum, and an increase in demand for food caused by a surge in population that is not comparable to the existing food supply. This paper aims to dig deeper about strengthening food security through the modernization of food barns departing from the Indonesian people’s local wisdom and the extent to which the modernization of food barns can be a solution in overcoming food insecurity due to not achieving food security. This paper uses descriptive qualitative research methods based on literature data, discussing alternative concepts to revitalize community food barns to maintain community and national food security stability. The concept being offered is to modernize community food granaries in terms of both management of stored foodstuffs and managerial aspects of community food storage management. Besides, it is necessary to develop cooperation to synergize between several food barns that are close to the community so that the working area coverage becomes wider.Keywords: management modernization, community food storage, food securityAbstrakPasca diterapkannya kebijakan revolusi hijau serta keberadaan Badan Urusan Logistik (Bulog) sebagai lembaga yang berperan menjaga kestabilan pangan, lumbung pangan masyarakat telah kehilangan eksistensinya. Dampak dari berkurangnya eksistensi lumbung pangan masyarakat tersebut dalam jangka panjang justru menyebabkan ketidakstabilan pangan di Indonesia. Hal ini disebabkan oleh beberapa faktor, di antaranya alih fungsi lahan pertanian menjadi lahan industri, penggunaan pupuk anorganik yang menyebabkan kesuburan lahan menurun sehingga menyebabkan hasil panen berkurang, terjadinya alih fungsi Bulog dari lembaga pemerintah menjadi BUMN/Perum, dan terjadinya peningkatan permintaan pangan yang disebabkan oleh peningkatan penduduk yang tidak sebanding dengan persediaan pangan yang ada. Tulisan ini bertujuan menggali lebih dalam tentang penguatan ketahanan pangan melalui modernisasi lumbung pangan yang bertolak dari kearifan lokal masyarakat Indonesia dan sejauh mana modernisasi lumbung pangan dapat menjadi solusi dalam mengatasi rawan pangan akibat belum tercapainya ketahanan pangan. Tulisan ini menggunakan metode penelitian kualitatif deskriptif berbasis data literatur, membahas alternatif konsep untuk merevitalisasi lumbung pangan masyarakat dalam upaya menjaga kestabilan ketahanan pangan masyarakat dan nasional. Konsep yang ditawarkan adalah memodernisasi lumbung pangan masyarakat baik dari segi pengelolaan bahan pangan yang disimpan, maupun aspek manajerial pengelolaan lumbung pangan masyarakat. Selain itu, perlu pengembangan kerja sama untuk bersinergi antar beberapa lumbung pangan masyarakat yang berdekatan dengan masyarakat sehingga cakupan wilayah kerjanya menjadi lebih luas.Kata kunci: modernisasi pengelolaan, lumbung pangan masyarakat, ketahanan pangan